The Determinants of Food Consumption Expenditure in Central Java - Economic Research Center, National Research and Innovation Agency (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
Food consumption is a basic human necessity that should be fulfilled. Although the investment level tends to increase in Central Java, the open unemployment rate also tends to increase. It is worrying that this condition will affect the society prosperity reflected by food security status. This research aims to analyze the consumption expenditure development in Central Java, identify the food consumption expenditure determinants, and formulate the food consumption fulfillment strategies. This research has quantitative characteristics by using the secondary data of Statistical Central Bureau. The research result shows the consumption expenditure proportion between food and non-food is nearly similar and tends to increase each year. The determinants, which affect the food consumption expenditure positively and significantly, are the non-food consumption expenditure, the gross domestic regional product (GDRP) of constant price, and the poverty rate. The food consumption fulfillment strategies in Central Java are directed by sustainability schemes covering economic, social, and environmental dimensions. The implementations are to strengthen the food security dimensions, the society income enhancement, the value chain optimization, the adoption of technology and knowledge, and the local food resources utilization